Trump 2.0 : the revolution that will permanently transform America - Spicer, Sean, 1971- (Regnery, an imprint of Skyhorse Publishing, Inc., 2026)
"President Donald J. Trump's second term in office will be the most consequential administration in history because of the people and the policies that are markedly different than his first term. While the Left and their conspirators in the media thought they had vanquished Trump after the 2020 election, the leader of the Make America Great Again movement didn't disappear as they had hoped. During President Biden's administration, Trump was assembling the people and building the policies that will forever change the direction of this country. He was not just preparing for his return to power. He was preparing for the revolution to permanently transform the country. President Trump has now returned to office, and this time his agenda will not be stopped. This time the president has the people and the policies to initiate historically unprecedented and monumental changes. From the border, to tariffs, to NATO, to DOGE, to the American people's health, and everything in between, this is not just another presidency. This is the battle for the future of the United States. This is the battle for the future of the world. This is Trump 2.0. Sean Spicer, the former communications director of the Republican National Committee, served as the 30th White House Press Secretary during President Trump's first term in office. His insider's look into Trump 2.0 is sure to inspire Republicans and infuriate Democrats. Above all, his landmark contribution to our understanding of President Trump's second administration is sure to leave a trail of controversy and debate in its wake."--